2014
DOI: 10.7150/ijms.9412
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Single Nucleotide Polymorphism in IL-4, IL-4R Genes and Systemic Concentration of IL-4 on the Incidence of Glioma in Iraqi Patients

Abstract: Glioma is the most common and believed to be one of the most aggressive tumors of the central nervous system (CNS) in humans. Very little information is available on the etiology and pathogenesis of these tumors to date. A significant gap remains in our current understanding of the molecular pathways involved in the genesis, progression and clinical behavior of these tumors. Recently, several single nucleotide polymorphisms (SNPs) have been identified in cytokine gene sequences, particularly within the promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 43 publications
0
11
0
3
Order By: Relevance
“…Of these 31 studies, 24 articles assessed the relationship between blood‐based inflammatory cytokines and glioma risk. Table presents the characteristics and quality evaluation of these 24 included studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these 31 studies, 24 articles assessed the relationship between blood‐based inflammatory cytokines and glioma risk. Table presents the characteristics and quality evaluation of these 24 included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Of these 24 studies, 10 examined IL‐6, five examined IL‐8, four examined interleukin‐17 (IL‐17), nine examined TNF‐ α , three examined transforming growth factor‐ β (TGF‐ β ), two examined CRP, three examined interleukin‐4 (IL‐4), five examined IL‐10, three examined interleukin‐12 (IL‐12), two examined interleukin‐23 (IL‐23), and four examined monocyte chemotactic protein‐1 (MCP‐1) . Among these 24 studies, serum samples from patients with glioma were collected in 22, and plasma samples were collected in the other two . Most of these studies used an enzyme‐linked immunosorbent assay (ELISA) to detect the concentrations of inflammatory cytokines, and only a few studies used other methods, such as bead array technology, fluorescence microsphere detection, xMAP, and radioimmunoassays .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several mechanisms could explain our findings. The T allele of IL‐4 rs2243250 polymorphism can increase binding of nuclear transcription factors to the promoter region of the IL‐4 gene and activate the transcription of genes involved in the pathogenesis of HT (Shamran et al, ). Further, Mazziotti et al showed a significant increase in CD4 + IL4 + cells in euthyroid patients with isolated HT (Mazziotti et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Among these, IL-4 rs2243250, rs2070874 and rs79071878 polymorphisms are three intensively studied variants. Previous studies have demonstrated that the T allele of IL-4 rs2243250 and rs2070874 polymorphisms can increase binding of nuclear transcription factors to the promoter region of the IL-4 gene, and thus lead to increased transcription of IL-4 ( 32 , 43 ). In addition, the rs79071878 polymorphism may also affect the transcription activity of IL-4 ( 54 ).…”
Section: Discussionmentioning
confidence: 99%